KEBIJAKAN INTEGRAL PERLINDUNGAN HUKUM ANAK KORBAN KEKERASAN SEKSUAL DI SATUAN PENDIDIKAN - Paikah Paikah; Dewi Angriani; Sadali (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2025)
This study analyzes the integral policy of legal protection for child victims of sexual violence within educational institutions. The research focuses on the forms of integral policies developed by local governments to protect child victims of sexual violence in schools, as well as the innovative measures and challenges faced by the government in providing such protection. The study employs an empirical legal research method with a case study approach. Both primary and secondary data were utilized and analyzed through a qualitative descriptive method in three stages: data reduction, data presentation, and conclusion drawing. The findings indicate that the government holds responsibility for protecting child victims of sexual violence in schools through affirmative policies that ensure special protection, as mandated by the Child Protection Law, the Human Rights Law, and the Sexual Violence Crime Law (UU TPKS). In essence, children are entitled to special assistance in the form of psychosocial services involving professionals across various fields to restore their mental well-being, including counseling, trauma therapy, social rehabilitation, and child mentoring. However, the implementation of psychosocial services in schools has not been effective due to several factors: the scope of protection has been limited to juridical aspects without addressing non-juridical dimensions, shortages of professional human resources, underperformance of school committees, lack of an integrated database of child victims, social stigma, low public awareness, and weak inter-institutional coordination. Efforts to enhance legal protection for child victims of sexual violence in educational institutions should be carried out through innovations in integral policies across juridical and non-juridical dimensions. This includes strengthening legal substance by establishing regional regulations on child sexual violence, improving legal structures through the creation of child support institutions in schools and supervisory committees on sexual violence, and cultivating legal culture by fostering awareness among parents, teachers, and communities. Commitment to protecting children from sexual violence must be built through effective communication among the three centers of education (family, school, and community), thereby ensuring that educational institutions become safe and child-friendly environments.